Private R&D not necessarily drawn to areas with high public R&D - Alexander Eickelpasch (DIW Economic Bulletin, 2016)
The bulk of Germany's research and development (R&D) activity is concentrated in densely populated areas, urban regions that account for 62 percent of the country's R&D workforce. The regions surrounding Stuttgart, Munich, and Braunschweig have by far the highest R&D intensity-that is, the share of R&D personnel in the total number of employees. Between 2003 and 2013, Munich lost some of its lead over the national average, while Stuttgart and Braunschweig increased their leads. In Germany on the whole, R&D personnel capacities in public research facilities and the higher education sector expanded more than did those in the business enterprise sector-not least due to the additional expenditure within the framework of certain government initiatives, namely the Pact for Research and Innovation, the German Universities Excellence Initiative, and the University Pact. The areas with the highest R&D intensity in public research (that is, research facilities and institutes of higher education) are Göttingen, Dresden, and Aachen-but only Dresden was able to increase its lead during the observation period. In the private sector, Stuttgart, Braunschweig, Darmstadt, and Ingolstadt have the highest R&D intensities. For private R&D, spatial proximity to manufacturing plays a much stronger role than does proximity to public R&D- hence areas with lower levels of industrial activity should not only promote the transfer of knowledge within the region but also take advantage of public research conducted elsewhere in order to support the local economy. Furthermore, to make better use of knowledge potential at the local level, regional industry should be strengthened-for example, within the framework of industrial development policy.
Keywords: O14; O30; O31; R12; 330; regional innovation systems; research and development; universities; research institutes; manufacturing; public expenditure